Communication and ritual at the comic book shop: The convergence of organizational and popular cultures. Issue 3 (8th October 2018) - Herrmann, Andrew F.
Abstract : Purpose: The purpose of this paper is to examine the rituals and communicative practices that simultaneously create community, out-groups and perceptions of stigma at a local comic book retail organization through autoethnography. As such this piece explores personal identity, comic book culture and how this comic book shop acts as important third place as defined by Oldenburg. Design/methodology/approach: Autoethnography allows for the simultaneous research into self, organizations and culture. As a layered account, this autoethnography uses narrative vignettes to examine a local comic book retail organization from the first person perspective of a collector, a cultural participant and geek insider. Findings: The term geek, once brandished as an insult to stigmatize, is now a sense of personal and cultural pride among members. Various rituals including the "white whale" moment and the specialized argot use help maintain community in the comic book shop creating a third place as categorized by Oldenburg. However, these shared communication practices and shared meanings reinforce the hegemonic masculinity of the store, leading the author to wonder if it can maintain its viability going forward. Originality/value: This autoethnography was performed at a local comic book shop, connecting communicative and ritual practices to organizational culture, hegemonic masculinity, geek culture and personal identity. It also argues that one need not be an embedded organizational insider to perform organizational autoethnography.